Coping Mechanisms as Predictor of Stress in Patients with Chronic Low Back Pain: A Nigerian Study - Asuquo, Joseph; Abang, Innocent; Anisi, Chukwuemeka; Toluse, Adetunji; Essien, Emmanuel; Edet, Bassey; Agweye, Pius (Nigerian Journal of Orthopaedics and Trauma, 2019)
Introduction: Chronic low back pain (LBP) is one of the most common musculoskeletal conditions worldwide. It can be quite severe, affecting physical, social, occupational and even psychological well‑being. This study describes the coping mechanisms commonly employed in patients with chronic LBP and its relationship to perceived stress. Methods: In this descriptive hospital‑based study, Brief Cope Scale and the Perceived Stress Scale (PSS) were administered to 100 patients with chronic LBP. Variables analysed were sociodemographic characteristics, dimensions of the Brief Cope Scale and the PSS. Logistic regression was used to determine predictors of perceived stress. Data were analysed using IBM SPSS version 20, and the threshold for statistical significance was set at 0.05. Results: Sample was comprised of 59 females and 41 males with an age range of 18–72 years (x̅ = 42.7 ± 16.2). The most common spinal pathologies were lumbar spondylosis (n = 39), canal stenosis (n = 18) and facet joint arthritis (n = 16). The average perceived stress score for the entire sample was 28 (standard deviation [SD] = 6.94), and the coping mechanisms most employed were religion (x̅ = 6.9, SD = 1.77), planning (x̅ = 6.4, SD = 1.34) and emotional support (x̅ = 6.0, SD = 1.54). After logistic regression, instrumental support, self‑blame, active coping, religion, positive reframing and venting emerged as predictors of perceived stress. Conclusion: Coping styles are an important determinant of perceived stress in patients with chronic LBP. Due consideration should be given to the stress experienced by patients with chronic LBP, and their clinical care should include stress management to improve outcome.